Unusual Brain MRI Pattern in 2 Patients with COVID-19 Acute Respiratory Distress Syndrome - Toledano-Massiah, S. (AJNR Am J Neuroradiol, 2020)
We report the cases of 2 patients hospitalized in our intensive care unit with confirmed coronavirus disease 2019 infection in whom brain MR imaging showed an unusual DWI pattern with nodular and ring-shaped lesions involving the periventricular and deep white matter. We discuss the possible reasons for these findings and their relationship to the infection.